.NET framework 4.5 expert programming cookbook. - Rajshekhar, A. P. (Packt Pub., 2013)
.Net Framework 4.5 Expert Programming Cookbook is a concise and practical cookbook with advanced recipes which demonstrate the new functionality of .NET Framework 4.5. If you are a .NET developer and would like to learn the new features in .NET 4.5, then this book is just for you. "".Net Framework 4.5 Expert Programming Cookbook"" gives developers with a basic to intermediate knowledge a high-level overview and clear understanding of what the .NET 4.5 Framework provides.